Product Quality Improvement of Stainless Steel Round Trash Can with Six Sigma Approach and Fuzzy Analytical Hierarchy process Method at PT. XYZ - Radinka Deena Zubaira; Wawan Kurniawan; Ratna Mira Yojana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
PT. XYZ is a manufacturing industry that produces various cleaning equipment. One of the products that has a high level of defects are trash bins made of stainless steel. The purpose of this research is to improve the quality of stainless steel waste products. The method used is Six Sigma and Fuzzy Analytical Hierarchy Process. In the Define stage, the types of defects found were body dents, scratches, spots, and rough covers. In the Measure stage, the initial DPMO value obtained is 3.422. In the Analyze stage, the results of the analysis process are defects with the highest Risk Priority Number of 280. The next stage is Improve, where defects with the highest RPN value are prioritized for proposed improvements using Fuzzy AHP. Based on the results of the Fuzzy AHP assessment, it was found that the highest weight was alternative 3, namely the machine must be cleaned regularly after being used at 0.4322, alternative 2, namely the addition of material handling to facilitate product transfer of 0.2048, and alternative 4, namely the establishment of SOPs for product handling. of 0.2041. After the Improve stage, the final stage in the form of Control is carried out to see whether the implementation of the proposed improvements has a positive impact on the company. The DPMO results obtained after implementation were 3.6061.